If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(y+8)=-5y
We move all terms to the left:
-4(y+8)-(-5y)=0
We multiply parentheses
-4y-(-5y)-32=0
We get rid of parentheses
-4y+5y-32=0
We add all the numbers together, and all the variables
y-32=0
We move all terms containing y to the left, all other terms to the right
y=32
| 3x-12=x-7 | | 10m=300 | | 1.5x-x=0.5+5 | | -2.5(x+4)=2.5x+12 | | 0=3x^2+8x-175 | | 9x+10=7x+32= | | 7m-12=9 | | 7m-13=9 | | 8x-59=37 | | 2x×3x=0 | | 4y+7=24 | | 5h+20=150 | | 4x+90=2x | | 5x+5+9=2×7-6x | | (5n-6)(n-8)=0 | | 2/5x+4=-3/5x-3 | | n^2+5n+2n+10=70 | | 4x-3/7+x=3 | | 7(3w+3)=12 | | 7+91x=39x=3 | | (2x-1)(4x+1)(1/3+2x)²=2/3(x-1/3)(1/3-2x)² | | 109=-v+163 | | x+45+45+50=180 | | 0=-6t2+48t | | -y+10=208 | | 2(4x-6)+14=50 | | r/5.7=2.3 | | 8m^2-64m=0 | | 8(3t−3)+2=−6 | | 175-v=51 | | 63/u=3 | | 2x-15=4x-5 |